Framework for Digital Transformation in SAP-Driven Cost Forecasting and Financial Reporting Systems - John Oluwaseun Olajide,; Bisayo Oluwatosin Otokiti,; Sharon Nwani,; Adebanji Samuel Ogunmokun,; Joyce Efekpogua Fiemotongha, (International Journal of Scientific Research in Science and Technology, 2024)
In today’s dynamic financial environment, the need for robust, agile, and data-driven financial systems has become paramount. This paper presents a comprehensive framework for digital transformation within SAP-based cost forecasting and financial reporting systems. Drawing from foundational enterprise resource planning architecture, the study first contextualizes the critical role SAP systems play in managing complex financial operations. It identifies persistent challenges in traditional implementations, such as data silos, manual processes, and limited real-time capabilities, which hinder financial visibility and strategic agility. The paper advances the discourse by defining digital transformation through core enablers such as automation, system integration, cloud computing, and intelligent analytics. It maps the evolution of financial reporting from manual processes to fully integrated, digitized systems and aligns this transformation with broader corporate digital strategies. The technical architecture of relevant SAP modules is examined in depth, along with the importance of system interoperability, data flow, and digital readiness for optimizing financial operations. A structured transformation framework is proposed, centered on four foundational pillars: data integration, process automation, intelligent analytics, and real-time reporting. The implementation roadmap is detailed across assessment, planning, pilot, scaling, and continuous improvement phases, while governance, risk, and compliance are embedded throughout to ensure regulatory alignment and auditability. The paper concludes by highlighting the strategic implications for financial leaders and suggests avenues for future research, including the integration of artificial intelligence and industry-specific adaptations. The framework serves as a vital resource for organizations aiming to enhance financial performance and resilience through digital transformation.
Keywords: SAP Financial Systems; Digital Transformation; Cost Forecasting; Financial Reporting; Intelligent Analytics; Governance and Compliance